2022
DOI: 10.3390/neurolint14010016
|View full text |Cite
|
Sign up to set email alerts
|

Serum CGRP Changes following Ultrasound-Guided Bilateral Greater-Occipital-Nerve Block

Abstract: Background: Calcitonin-gene-related peptide (CGRP) and CGRP receptors are expressed in trigeminal nerve cells, and treatments targeting CGRP are effective in migraines. For headaches that do not respond to pharmacological treatment, minimally invasive techniques such as greater-occipital-nerve block (GONB) can help relieve the pain and reduce the frequency of headaches. Our study assessed the efficacy of ultrasound-guided greater-occipital-nerve block (USgGONB) in chronic migraines (CM) and its relationship to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…§Odd's ratio 95%CI: 95% confidence interval. for migraine, after ultrasound-guided bilateral GONB compared to pre-blockade level (28). Similarly, improvement in neurophysiological correlates of CM following GONB has been reported (29).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…§Odd's ratio 95%CI: 95% confidence interval. for migraine, after ultrasound-guided bilateral GONB compared to pre-blockade level (28). Similarly, improvement in neurophysiological correlates of CM following GONB has been reported (29).…”
Section: Discussionmentioning
confidence: 69%
“…In fact, a previous study showed that the effect of single GONB lasts far longer than its anesthetic effect (13). Though the exact mechanisms of such modulations remain unknown, a clinical study has shown a significant drop in interictal serum CGRP levels, a biomarker for migraine, after ultrasound-guided bilateral GONB compared to pre-blockade level (28). Similarly, improvement in neurophysiological correlates of CM following GONB has been reported (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our literature analysis (Table 1 ) shows that studies based on CGRP determinations are highly variable in terms of measuring method and study design, including sample source, sample processing, inclusion/exclusion criteria for patients and controls and aim of the study [ 14 , 15 , 19 , 31 , 39 , 42 , 60 , 66 , 68 ]. Data analysis and presentation of laboratory determinations is also changeful, which hinder the comparison of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Such diaries, while obviously not on par with clinical assessments, are well documented and used routinely in clinical studies for longer-term evaluations. 46 Table 2 provides the details regarding primary and secondary outcomes, and it should be considered that the median values in this table are confined to sessions that resulted in successful blockade, thus greatly underestimating the true difference between both drugs.…”
Section: Discussionmentioning
confidence: 99%